2009
DOI: 10.2337/dc09-1143
|View full text |Cite
|
Sign up to set email alerts
|

Day Napping and Short Night Sleeping Are Associated With Higher Risk of Diabetes in Older Adults

Abstract: OBJECTIVETo examine whether day napping or short night sleeping is associated with higher risk of diabetes.RESEARCH DESIGN AND METHODSThis was a prospective study of hours of day napping and night sleeping assessed in 1996–1997 in relation to diabetes diagnosed between 2000 and 2006 (n = 10,143) among 174,542 participants in the National Institutes of Health (NIH)-AARP Diet and Health Study. Odds ratios (ORs) and 95% CI were derived from multivariate logistic regression models.RESULTSLonger day napping was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
133
8
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(161 citation statements)
references
References 24 publications
16
133
8
4
Order By: Relevance
“…A recent meta-analysis combining data from 90,623 individuals concluded that for short sleep duration (#5-6 h per night), the relative risk of developing diabetes was 1.28 after controlling for multiple factors (17). Not included in this meta-analysis is the largest study to date (18), which included 174,542 adults and observed that individuals who report sleeping <5 h per night, relative to those reporting 7-8 h per night, had a 46% higher risk of developing type II diabetes, after controlling for multiple confounders, including adiposity.…”
Section: Epidemiologic Evidence For a Link Between Sleep Disturbancesmentioning
confidence: 99%
“…A recent meta-analysis combining data from 90,623 individuals concluded that for short sleep duration (#5-6 h per night), the relative risk of developing diabetes was 1.28 after controlling for multiple factors (17). Not included in this meta-analysis is the largest study to date (18), which included 174,542 adults and observed that individuals who report sleeping <5 h per night, relative to those reporting 7-8 h per night, had a 46% higher risk of developing type II diabetes, after controlling for multiple confounders, including adiposity.…”
Section: Epidemiologic Evidence For a Link Between Sleep Disturbancesmentioning
confidence: 99%
“…In addition, without a dose-response analysis, it remains unknown how many hours of habitual sleep are associated with the lowest risk of type 2 diabetes. In the past several years, the number of prospective studies with enough quantitative categories has nearly doubled (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Therefore, we conducted a meta-analysis of prospective studies to determine the overall shape of the relationship between sleep duration and risk of type 2 diabetes.…”
mentioning
confidence: 99%
“…Compelling epidemiological evidence suggests a link between insufficient sleep and an increased risk of high BMI, obesity and/or type 2 diabetes [61][62][63][64]. Combining data obtained from 90 623 individuals, Cappuccio et al concluded that individuals who report sleeping less than 5 h each night have a 46% higher risk of developing type 2 diabetes compared to individuals who sleep 7-8 h each night [64].…”
Section: Sleep Deprivation and The Effect On Metabolismmentioning
confidence: 99%